Pengaruh Word of Mouth, Kualitas Pelayanan, Persepsi Harga dan Pengalaman Pelanggan Terhadap Keputusan Pelanggan Untuk Menggunakan Jasa Salon Jay di Patikraja - Resa Tri Wulandari; Tri Esti Masita; Wisnu Wijayanto (ProBisnis : Jurnal Manajemen, 2026)
This study examines the influence of word of mouth, service quality, price perception, and customer experience on the decision to use services at Salon Jay in Patikraja. Data were collected from 100 customers through accidental sampling and analyzed using multiple linear regression. The results show that all four variables have a positive and significant effect on customer decisions, with a coefficient of determination (R²) of 0.587. The regression model was found to be feasible based on the F-test. Practical implications suggest that management should enhance word-of-mouth communication, service consistency, perceived value, and emotional engagement. Future research may include additional variables such as promotion, facilities, and digital marketing to better understand customer decision-making.